Oligometastases to the liver: predicting outcomes based upon radiation sensitivity - Qiu, Haoming; Katz, Alan W.; Milano, Michael T. (Journal of Thoracic Disease, 2016)
Liver metastases from solid tumors such as colon, rectum, pancreas, lung and breast are a major cause of mortality and morbidity in patients with cancer.